Mycobacterium tuberculosis Protein PE6 (Rv0335c), a Novel TLR4 Agonist, Evokes an Inflammatory Response and Modulates the Cell Death Pathways in Macrophages to Enhance Intracellular Survival - Sharma, Neha; Shariq, Mohd; Quadir, Neha; Singh, Jasdeep; Sheikh, Javaid A.; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (M. tb) is an intracellular pathogen that exploits moonlighting functions of its proteins to interfere with host cell functions. PE/PPE proteins utilize host inflammatory signaling and cell death pathways to promote pathogenesis. We report that M. tb PE6 protein (Rv0335c) is a secretory protein effector that interacts with innate immune toll-like receptor TLR4 on the macrophage cell surface and promotes activation of the canonical NFĸB signaling pathway to stimulate secretion of proinflammatory cytokines TNF-α, IL-12, and IL-6. Using mouse macrophage TLRs knockout cell lines, we demonstrate that PE6 induced secretion of proinflammatory cytokines dependent on TLR4 and adaptor Myd88. PE6 possesses nuclear and mitochondrial targeting sequences and displayed time-dependent differential localization into nucleus/nucleolus and mitochondria, and exhibited strong Nucleolin activation. PE6 strongly induces apoptosis via increased production of pro-apoptotic molecules Bax, Cytochrome C, and pcMyc. Mechanistic details revealed that PE6 activates Caspases 3 and 9 and induces endoplasmic reticulum-associated unfolded protein response pathways to induce apoptosis through increased production of ATF6, Chop, BIP, eIF2α, IRE1α, and Calnexin. Despite being a potent inducer of apoptosis, PE6 suppresses innate immune defense strategy autophagy by inducing inhibitory phosphorylation of autophagy initiating kinase ULK1. Inversely, PE6 induces activatory phosphorylation of autophagy master regulator MtorC1, which is reflected by lower conversion of autophagy markers LC3BI to LC3BII and increased accumulation of autophagy substrate p62 which is also dependent on innate immune receptor TLR4. The use of pharmacological agents, rapamycin and bafilomycin A1, confirms the inhibitory effect of PE6 on autophagy, evidenced by the reduced conversion of LC3BI to LC3BII and increased accumulation of p62 in the presence of rapamycin and bafilomycin A1. We also observed that PE6 binds DNA, which could have significant implications in virulence. Furthermore, our analyses reveal that PE6 efficiently binds iron to likely aid in intracellular survival. Recombinant Mycobacterium smegmatis (M. smegmatis) containing pe6 displayed robust growth in iron chelated media compared to vector alone transformed cells, which suggests a role of PE6 in iron acquisition. These findings unravel novel mechanisms exploited by PE6 protein to subdue host immunity, thereby providing insights relevant to a better understanding of host–pathogen interaction during M. tb infection.